2022
DOI: 10.1038/s41598-022-06776-6
|View full text |Cite
|
Sign up to set email alerts
|

Weak antilocalization, spin–orbit interaction, and phase coherence length of a Dirac semimetal Bi0.97Sb0.03

Abstract: The present study develops a general framework for weak antilocalization (WAL) in a three-dimensional (3D) system, which can be applied for a consistent description of longitudinal resistivity $$\rho_{xx} \left( B \right)$$ ρ xx B and Hall resistivity $$\rho_{xy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…From figure 4(a), it is observed that, the MR% varies linearly with applied magnetic field producing a v-type shape around low field for un-doped Bi 2 Te 3 . This v-type cusp at low field is a signature of quantum features named as weak anti-localization (WAL) effect [5][6][7][8][9][10][11][12][13][14][15]. Because of intrinsic spin-orbit interaction (SOI) in host Bi 2 Te 3 , two self-interacting time-reversal paths of electrons destructively quantum interfere.…”
Section: Magneto-transport Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…From figure 4(a), it is observed that, the MR% varies linearly with applied magnetic field producing a v-type shape around low field for un-doped Bi 2 Te 3 . This v-type cusp at low field is a signature of quantum features named as weak anti-localization (WAL) effect [5][6][7][8][9][10][11][12][13][14][15]. Because of intrinsic spin-orbit interaction (SOI) in host Bi 2 Te 3 , two self-interacting time-reversal paths of electrons destructively quantum interfere.…”
Section: Magneto-transport Analysismentioning
confidence: 99%
“…Topological state of quantum materials (QMs) is one of the latest inventions of twenty-first century in condensed matter physics [1][2][3][4][5][6][7][8][9]. Topological insulator (TI) possesses an unconventional identity as there exists both insulating and metallic nature in the same material.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Excited-state intramolecular charge transfer (ICT) has attracted extensive attention for in-depth understanding of the fundamental deactivation processes and key mechanisms in photochemistry and photobiology. 1–5 The ICT processes are sensitive to the intermolecular hydrogen bond interactions between solute and solvent molecules as an important external factor. 6–9…”
Section: Introductionmentioning
confidence: 99%
“…Excited-state intramolecular charge transfer (ICT) has attracted extensive attention for in-depth understanding of the fundamental deactivation processes and key mechanisms in photochemistry and photobiology. [1][2][3][4][5] The ICT processes are sensitive to the intermolecular hydrogen bond interactions between solute and solvent molecules as an important external factor. [6][7][8][9] To explore the inuence of intermolecular hydrogen bonds on the excited-state dynamics, [10][11][12][13][14][15] the Kamlet-Ta (K-T) solvatochromic parameters (p*, a, b) have been developed to depict the hydrogen bond interaction between solute and solvent molecules and to depict the spectral redshi in the steady-state absorption and uorescence spectroscopy induced by solvents.…”
Section: Introductionmentioning
confidence: 99%